Torn / 4. - Haddix, Margaret Peterson (Missing, 2011)
Time travelers Jonah and Katherine arrive in 1611 to rescue John Hudson, the missing son of explorer Henry Hudson, but just as the mutiny on the "Discovery" is supposed to start, Jonah and Katherine's knowledge of history is tested once again and they fear that more is at stake than just one boy's life. Includes facts about Henry Hudson's explorations.